Factors Affecting Health Information System Quality: Can Top Management Support Be A Moderator? (Public Accounting and Sustainability, 2024)
Research aims: This study aims to examine the factors that influence the quality of health information system (HIS) in hospitals in Bandung City and top management support as a moderating variable. Design/Methodology/Approach: This research method is a survey. Eighty-three users of HIS in hospitals participated as respondents. Hypotheses were tested using the partial least squares structural equation modeling (PLS-SEM) method. Research findings: The study results exhibited that software quality did not affect the health information system quality, even if it was moderated by top management support. While user competence significantly impacted health information system quality, top management support would strengthen the influence between user competence and health information system quality. Theoretical contribution/Originality: This study presents a conceptual framework for HIS quality, with a specific emphasis on the role of top management support. Practitioner/Policy implication: This study recommends that HIS should have interoperability. Additionally, there is a need for government policy support at both central and regional levels to ensure that the hospitals’ top management demonstrates a real commitment and contribution.